2022
DOI: 10.1136/bmjopen-2022-060822
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of a virtual reality tool for the treatment of obesity: study protocol of a randomised controlled trial

Abstract: IntroductionPrevious research has shown that it is feasible to integrate motivational interviewing techniques with behavioural and psychological interventions for the treatment of obesity. Moreover, these combined interventions have the potential to improve health-related outcomes of people living with obesity (PLWO) and to afford maintenance of behavioural changes over time. In addition, the use of virtual reality (VR) embodiment techniques in the treatment of eating disorders and obesity has promising prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The basic goal of the training was to help participants organize their future self-conversation so they would be able to guide themselves through a discourse of change based on their values and interests. More details about the contents of the training can be found in the protocol study ( 27 ) while the behavioral change techniques used in the intervention can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic goal of the training was to help participants organize their future self-conversation so they would be able to guide themselves through a discourse of change based on their values and interests. More details about the contents of the training can be found in the protocol study ( 27 ) while the behavioral change techniques used in the intervention can be found in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…All inclusion and exclusion criteria were assessed through an initial clinical interview by clinical researchers of the team. More detailed information about this procedure can be found in the publication of the RCT protocol ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, VR can be leveraged as a treatment tool to support behavior modi cation and promote healthy eating habits by reinforcing these goals in lifelike virtual scenarios. Moreover, VR has been applied in treating eating disorders (EDs) and obesity, leading to decreased food cravings, better body image, and improved emotion regulation abilities (13). Anastasiadou et al (14), also found that VR can aid individuals with obesity by boosting their readiness to change habits, increasing self-e cacy, and reducing dysfunctional eating behaviors and anxiety.…”
Section: Intruductionmentioning
confidence: 99%